How’s My English? The English Communication Needs of Wellness Spa Therapists in Thailand - Kraisri, Jidapha; Deocampo, Marilyn Fernandez (ABAC ODI JOURNAL Vision. Action. Outcome, 2021)
This study focuses on the English communication needs of wellness spa therapists in Thailand. This is supported by an objective: to identify the needs of spa therapists in English communication specifically to the target situation. This study is deemed important so that a specific English language course can be recommended. The study employed a qualitative method employing observation and semi-structured interviews as instruments to collect data and used purposive sampling to select the participants. There were 30 spa therapists and one assistant manager participated in this study. The findings revealed that spa therapists have different needs with regards to English communication in the target situation. This includes 1) the needs for familiarization of the basic English pronunciation; 2) the needs for knowing specific vocabularies while dealing with customers’ situation and needs, and 3) the needs for knowing different phrases and sentences to construct different word-formation. The implication based on the findings, therefore, is that, pedagogically, it is recommended that, ideally, a course should be developed for the spa therapists that can focus on the English language communication that could help them with specific vocabularies, words, and phrases to be used in the target situation. Consequently, as wellness centers are normally visited by people from different part of the world, the aim therefore should not be on the English language alone but varieties of English that people used globally, so that spa therapists would know ‘what words to be used’, ‘how words should be used’ and ‘what context should be used.